METODE YADAWI DAN IDENTIFIKASI MEMUDAHKAN MENGHAFAL KETENTUAN WARIS DI DALAM AL-QUR’AN - Wijayanti, Henni; Windiani, Arofah; Muhammad, A. Azis (E-Journal Widya Yustisia, 2017)
Islam is the way of life and the law of inheritance is one of the components of Islamic law and it’s in particular was revealed by Allah swt through His Prophet. Allah Swt has explained the details of inheritance law through Qur’an (4: 11, 12, 176), based on the verses are difficult to memorized. The study is focused to introduces the Yadawi and Identification method, the methods to make much easier to understand and to memorized the verses of inheritance.The methodology used in this study is the empirical qualitative method where the verses are analyzed and based on the experience for many years. Through these metod, it is hoped that Muslims can easily implement the law of inheritance. So, there is no reason and no excuse whatsoever not to apply the Islamic law of inheritance which is based on Qur’an.